ANALISIS BIAYA KEMACETAN LALU LINTAS BERDASARKAN ASPEK BIAYA OPERASIONAL KENDARAAN (STUDI KASUS : JL AHMAD YANI - JL RAYA CILEUNYI BANDUNG) - Nada Nurul Karimah, - (2022)
High community activity on Ahmad Yani street through Cileunyi street brings frequent traffic jams to happen in the morning and evening. Traffic jams make an impact to transportation user directly and indirectly. When there is a traffic jam, the vehicle will experience a discrease in speed even to the point of stopping. If the vehicles run into hindrance then the use of fuels, lubricants and other components that are wasted will be more as well as higher maintenance cost lead to the higher vehicle operating cost. Large vehicles operating costs if calculated with the time losses then there will also be a large traffic jams cost. Therefore to overcome traffic jams at Ahmad Yani street though Cileunyi street, there is a need for alternative modes of public transportation that are capable of serving the community economically, safely, and comfortably. It is hoped that people who use private vehicles will switch into public transportation, so the cost of traffic jams will be reduced. Based on the result of the congestion costs obtained at each point, cost from Ahmad Yani Street is Rp. 10.165.584, Ujung Berung Street is Rp. 236.084 , Cibiru Street is Rp. 123.290 and Cileunyi Street is Rp. 13.596.304. After analyzing the selection of transportation modes by switching private vehicles to public transportation, it is obtained the logit biner deviation is Pa = 1/(1+〖 exp〗^(3,7804+0,0009452 (Csm-Csa)) and Pa = 1/(1+〖 exp〗^( -0,1544188+0,000006 (Ckr-Csa)). From the equation, it is obtained that the difference in the cost of motorcycle to public transportation is Rp. 6.200 and passenger cars to public transportation is Rp 32.000. The volume of motorcycle is reduced by 90% and passenger cars is reduced by 90%. The cost of traffic jams is reduced by Rp. 13.492.255 or 99,23% of the previous scheme in one day.